83.1k views
5 votes
A sin^3theta+b cos^3theta=sintheta costheta and a sintheta-b costheta=0 then prove a^2+b^2=1​

User Arthur Kim
by
4.5k points

1 Answer

2 votes

Answer:

Proof in explanation

Explanation:

Trigonometric Identities

The basic trigonometric identity is:


\sin^2\theta+\cos^2\theta=1

We'll use it and some basic algebra to prove that, given:


a sin^3\theta+b cos^3\theta=sin\theta cos\theta

And


a\sin\theta-b\cos\theta=0

Then


a^2+b^2=1

From the equation:


a\sin\theta-b\cos\theta=0

We have:


a\sin\theta=b\cos\theta\qquad [1]

The equation


a sin^3\theta+b cos^3\theta=sin\theta cos\theta

Can be rewritten as


a\sin\theta \sin^2\theta+b \cos^3\theta=\sin\theta \cos\theta

Replacing [1]:


b\cos\theta \sin^2\theta+b \cos^3\theta=\sin\theta \cos\theta

Taking the common factor:


b\cos\theta (\sin^2\theta+ \cos^2\theta)=\sin\theta \cos\theta

The expression in parentheses is 1, thus:


b\cos\theta =\sin\theta \cos\theta

Dividing by
\cos\theta


b=\sin\theta

Replacing in


a\sin\theta=b\cos\theta

We have


a\sin\theta=\sin\theta\cos\theta

Dividing by
\sin\theta


a=\cos\theta

Now:


a^2+b^2=(\cos\theta)^2+(\sin\theta)^2

This expression is 1, thus it's proven:


\boxed{a^2+b^2=1}

User Roko Mijic
by
5.0k points